The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.orglett.0c01899
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Suzuki Coupling/Intramolecular Oxetane Ring Opening to Form Polycyclic Ring Systems

Abstract: A tandem one-pot reaction featuring a cross-coupling followed by an intramolecular oxetane ring opening by mild nucleophiles is reported. The overall transformation comprises a carbon−carbon bond formation along with a carbon−heteroatom bond construction providing diverse multicyclic ring systems with a pendant hydroxymethyl handle for further elaboration. This approach constitutes a convergent method for rapid access to various scaffolds. Furthermore, a comparison of computed low-energy conformers is presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…6 Kuduk and co-workers used tandem Suzuki coupling/intramolecular oxetane ring opening to prepare polycyclic systems. 7 Rosei and co-workers reported the tandem desulfurization/C− C coupling reaction for synthesis of the pentacene and an exotic ladder polymer. 8 These studies demonstrated that tandem reactions can provide high efficiency and selectivity in the synthesis of compounds or polymers.…”
mentioning
confidence: 99%
“…6 Kuduk and co-workers used tandem Suzuki coupling/intramolecular oxetane ring opening to prepare polycyclic systems. 7 Rosei and co-workers reported the tandem desulfurization/C− C coupling reaction for synthesis of the pentacene and an exotic ladder polymer. 8 These studies demonstrated that tandem reactions can provide high efficiency and selectivity in the synthesis of compounds or polymers.…”
mentioning
confidence: 99%
“…This approach would allow for selective formation of the desired regioisomer based on the selection of the aryl halide starting material. Aligned with our previous work on one-pot reactions employing the ring opening of oxetanes under basic conditions, , herein we report a tandem C–N coupling followed by oxetane ring opening to access benzomorpholine and tetrahydroquinoxaline scaffolds. In addition to the generation of these valuable heterocyclic motifs, a pendant hydroxymethyl group is revealed for further derivatization.…”
mentioning
confidence: 58%
“… 11 , 12 This intramolecular cyclization strategy has been successfully employed for the synthesis of heterocycles from prefunctionalized oxetane intermediates. 13 , 14 In particular, Sun has exploited this in the enantioselective syntheses of heterocycle derivatives employing a chiral phosphoric acid catalyst. This has included the enantioselective synthesis of 1,4-dioxanes from preformed hydroxy-ether-containing oxetanes ( Figure 1 C).…”
mentioning
confidence: 99%